Professional sports in Russia: challenges for modern government control model - Opletin, A. A.; Urasova, A. A.; Zubarev, N. Y. (Theory and Practice of Physical Culture, 2017)
Presently national sports are viewed as a powerful tool to advance patriotism in the country and an excellent field for efficient government control to secure due return on the governmental investments in form of competitive accomplishments, public support and enthusiasm of national athletes. At this juncture the Russian government builds up an integrated professional sport system in the country albeit the initiative is largely hampered by the still underdeveloped legal and regulatory framework and the high dependence of the system on the government budgets. These problems are commonly acknowledged as barriers for the sustainable and independent professional sport system building initiatives in the Russian Federation. Our study was designed to outline a government control model for the professional sport system and its resource development avenues. We applied a structure-and-functionality analysis to identify the key actors and their responsibilities and to model their interactions within the proposed government control model for professional sports. The model specifies the key control instruments of the professional sport sector. Our analysis of the proposed model made it possible to highlight the key problems in the government control of the sector that need to be solved to help the national professional sport sector cope with the crisis it is presently facing.